RESULTS OF THE MODIFIED LEFT VENTRICLE RECONSTRUCTION WITH EVALUATION OF GEOMETRIC PARAMETERS IN POSTINFARCTION ANEURYSM OF THE HEART - V. E. Babokin; V. P. Pronina; Yu. V. Mishchenko; V. A. Ananko; M. A. Martakov (Российский кардиологический журнал)
Modern times, surgeons of the entire world utilize the technics of left ventricular reconstruction (LVR) developed by professor Dor V. However, oftenly the left ventricle (LV) presents with a spheric shape in postoperation period, by echocardiography. When, normally, geometry of the LV is conceptualized as a stretched ellipse with longitudinal axis directed from apex to the base of the heart.Aim. To evaluate effectiveness of modified LVR using Z-suture to create the LV apex in patients with postinfarction heart aneurysms.Material and methods. Twelve patients with anterior-septal localization of the LV aneurysm having myocardial infarction in anamnesis more than 6 months, with LV ejection fraction less 45%, underwent the modified LVR with Z-suture. Efficacy of the correction was assessed by echocardiography data in short term period till 1 month after the operation, comparing with pre-surgery data.Results. In all patients surgery proceeded successfully. Sphericity index significantly decreased in diastolic phase at basal level from 0,83±0,17 to 0,63±0,11 (p=0,05) and at apical level from 0,56±0,12 to 0,37±0,09 (p=0,01). Conical index increased at basal level from 1,26±0,06 to 1,67±0,40 (p=0,05), at middle-apical level from 1,34±0,30 to 1,4±0,34 (p=0,05).Conclusion. The modified left ventricular reconstruction with Z-suture forms the ellipsoid heart shape and is an effective method of surgery of postinfarction LV aneurysm.